2021
DOI: 10.1021/acs.biochem.0c00923
|View full text |Cite
|
Sign up to set email alerts
|

The Size and Stability of Infectious Prion Aggregates Fluctuate Dynamically during Cellular Uptake and Disaggregation

Abstract: Prion diseases arise when PrP Sc , an aggregated, infectious, and insoluble conformer of the normally soluble mammalian prion protein, PrP C , catalyzes the conversion of PrP C into more PrP Sc , which then accumulates in the brain leading to disease. PrP Sc is the primary, if not sole, component of the infectious prion. Despite the stability and protease insensitivity of PrP Sc aggregates, they can be degraded after cellular uptake. However, how cells disassemble and degrade PrP Sc is poorly understood. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Nanoparticles (NPs) are widely used as drug carriers, in cancer targeting therapy, in catalysis, and in bioimaging. The delivery efficacy of NPs depends mainly on their interaction with cell membranes and uptake mechanisms . The regulation of interaction between NPs and cells is an important prerequisite for their application in disease treatment and diagnosis. To date, extensive studies have confirmed that the physicochemical properties (e.g., size, shape, composition, and surface charge) of NPs have profound impacts on the cellular interactions and uptake processes. Therefore, understanding the NP physicochemical properties and their impacts on cellular uptake and pathways is important for the design of optimal drug-delivery nanocarriers.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles (NPs) are widely used as drug carriers, in cancer targeting therapy, in catalysis, and in bioimaging. The delivery efficacy of NPs depends mainly on their interaction with cell membranes and uptake mechanisms . The regulation of interaction between NPs and cells is an important prerequisite for their application in disease treatment and diagnosis. To date, extensive studies have confirmed that the physicochemical properties (e.g., size, shape, composition, and surface charge) of NPs have profound impacts on the cellular interactions and uptake processes. Therefore, understanding the NP physicochemical properties and their impacts on cellular uptake and pathways is important for the design of optimal drug-delivery nanocarriers.…”
Section: Introductionmentioning
confidence: 99%